The importance of structure and trust in developmental work in school: with observations and joint analyses as the key activity - Postholm, May Britt (Frontiers in Education, 2025)
Organizational conditions and social aspects as requirements for learning, and faculty trust has been highlighted as the foundation for collaboration and school development. The professional development of teachers plays a crucial role in improving teachers teaching together with the pupils. But how development work is organized and how faculty trust is aimed for are scarcely described in the literature. This article is based on a qualitative study conducted in the frame of cultural historical activity theory (CHAT), focusing on school development in one primary school with nine teachers and two leaders: one principal and one middle leader. The problem formulation for the study presented in the article was the following: How do teachers experience participation in a developmental work research project designed by researchers within the frame of CHAT? The study describes how processes leading to a joint focus can be arranged, and how structured analyses of observed teaching can lead to professional dialogues and the development of trust. The study shows that the teachers wanted to continue with observation and joint analyses after the project ended but noted that the principal must facilitate such processes.